The Influence Of Financial Performance On Company Value - Febriana, Amanda; Sofyaun, Ashari; Matyani, Matyani (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to determine the Influence of Financial Performance with the proxy Current Ratio, Debt to Equity Ratio, Return on Assets on Company Value with the proxy Price to Book Value as the objective of the study. The study was conducted on food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. The sample selection was carried out using the purposive sampling technique and obtained 32 companies, with a total observation data of 128. The findings of the study showed that liquidity had no effect, while leverage and profitability partially succeeded in positively influencing company value.